2022
DOI: 10.1186/s12905-022-01738-6
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders and their relationship with menopausal phases among a sample of middle-aged Lebanese women

Abstract: Objectives The objective of our study was to evaluate the association between the transition to menopause, body dissatisfaction, and abnormal eating habits (restrained eating, binge eating, and orthorexia nervosa) in a sample of middle-aged Lebanese women. Methods A cross-sectional study conducted between July 2019 and January 2020 enrolled 1001 women aged 40 years and above from all Lebanese governorates. Data were collected by face-to-face interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…When excluding the previously mentioned micro-longitudinal pilot study which only included 8 participants, 64 the sample size of eligible studies ranged from n = 67 90 to n = 1001, 80 with an average of 387 participants (SD = 291). As presented in Table 1, the age range required for inclusion was generally between 40 and 65 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When excluding the previously mentioned micro-longitudinal pilot study which only included 8 participants, 64 the sample size of eligible studies ranged from n = 67 90 to n = 1001, 80 with an average of 387 participants (SD = 291). As presented in Table 1, the age range required for inclusion was generally between 40 and 65 years.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, they did not find significant differences when using scores from the EDI body dissatisfaction subscale ( p ⩾ .05) or the level of satisfaction with weight ( p ⩾ .05). 99 Khalil et al 80 found that body dissatisfaction was higher in perimenopausal ( p = .002) and postmenopausal ( p = .003) women compared to premenopausal women, while Gümüşsoy et al 82 found higher levels of body dissatisfaction in the postmenopausal group compared to the perimenopausal group ( p < .001). McLaren et al 67 also found that menopausal status at age 54 years was significantly associated with weight esteem ( p = .016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Careful attention must be given to review any medications, as many drugs can cause weight gain, such as nonhormonal treatments for hot flashes including gabapentin and selective serotonin reuptake inhibitors. In addition to cancer screening, proper screening for mental health conditions including anxiety, depression, and disordered eating, specifically orthorexia and binge eating disorder, is also recommended [17]. Based on screening results, referring to a mental health provider may also be needed.…”
Section: Key Pointsmentioning
confidence: 99%